Pengembangan Media Kartu Tajwid Berbasis TTS dalam Meningkatkan Pemahaman Siswa Madrasah Ibtidaiyah - Firdaus, Itsnayni Aniysah; Nadlir, Nadlir; Ernawati, Novi; Zahroh, Tsalista Lathivatuz (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
This study aims to develop tajweed card media based on crossword puzzles (TTS), through the use of this tajweed card media to provide understanding to students related to tajweed learning. The methods used in this study include the Research and Development (R&D) research method with the ADDIE model. In product development, we chose the test research subjects to be media experts and material experts as well as 10 students as a test of the effectiveness of tajweed TTS card media. The collection techniques that researchers use are observation, interviews, and questionnaires. As this instrument is used to find the validity of the media and material on media products, namely by using the instrument of media experts and material experts. The results showed that this TTS-based tajweed card media product received a material validity percentage value of 82%, and received a media percentage value of 86%, then the trial on students received an average score of 70. With this, it can be concluded that this TTS-based tajweed card media is declared effective.Keyword : Card Media; TTS Based Card; Students' Tajweed Understanding